Deslocamento de abomaso em vacas leiteiras: revisão bibliográfica - Oliveira, Mayara Porcari (2022)
In this review, themes about the importance of abomasal displacement in dairy cows were discussed. For this, we used information from several sources, including research institutions, specialized websites, national and international journals, technical bulletins, articles published in national and international journals and books. Abomasum displacement (AD) is an increasingly frequent problem in specialized herds around the world and, therefore, it is extremely important to understand its causes in order to prevent it. In addition, it is essential to know how to diagnose and treat this disease. In the pathology, as the name indicates, the abomasum is displaced from its normal anatomical position on the abdominal floor. The affected animal presents a sudden decrease in appetite, apathy, dehydration, peripheral ischemia, and usually diarrhea. The occurrence of displacement is associated with acute ketosis, laminitis and postpartum mastitis. Abomasal displacement causes economic losses in dairy herds through treatment costs, premature slaughter and loss of production. The condition is mainly observed in dairy cows 3 to 4 weeks after parturition and its incidence can be reduced by good management of the animals in the peripartum.